2014
DOI: 10.1088/1757-899x/64/1/012010
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and moisture barrier properties of titanium dioxide nanoparticles and halloysite nanotubes reinforced polylactic acid (PLA)

Abstract: Abstract. Polylactic acid (PLA) has been larger used in biomedical field due to its low toxicity and biodegradability. The aim of this study was to produce PLLA nanocomposites, by melt extrusion, containing Halloysite nanotubes (HNT) and/or titanium dioxide (TiO 2 ) nanoparticles. Immediately after drying, PLLA was mechanically homogenized with the nanofillers and then melt blended using a single screw extruder (L/D = 30) at a speed of 110 rpm, with three heating zones in which the following temperatures were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…The silane treatment was effective in decreasing the WVTR at a lower concentration of ZnO NP impregnation due to the uniform distribution of NPs in the PLA matrix [ 43 ]. Clays can also provide gas and water vapour resistance and increase the biopolymer’s mechanical strength [ 58 ]. The reinforcement of TiO 2 and HNT NPs revealed a unique trend parallel to a greater hydroxyl groups on the surface of the NPs, enhancing the mass transfer of water molecules through the matrix, thereby increasing the WVTR.…”
Section: Characterisation Of Pla-based Ncs Reinforced With Inorganmentioning
confidence: 99%
“…The silane treatment was effective in decreasing the WVTR at a lower concentration of ZnO NP impregnation due to the uniform distribution of NPs in the PLA matrix [ 43 ]. Clays can also provide gas and water vapour resistance and increase the biopolymer’s mechanical strength [ 58 ]. The reinforcement of TiO 2 and HNT NPs revealed a unique trend parallel to a greater hydroxyl groups on the surface of the NPs, enhancing the mass transfer of water molecules through the matrix, thereby increasing the WVTR.…”
Section: Characterisation Of Pla-based Ncs Reinforced With Inorganmentioning
confidence: 99%
“…The addition of CNFs into the PLA matrix was found to significantly increase the mechanical properties of the BNs. 15 The previous studies showed that the addition of both the CNFs and nano-TiO 2 generally increased the mechanical properties of the PLA and PHB composites. 8,16,43,44 As a result, it can be said that the addition of the fillers had a positive effect on the mechanical properties of each biopolymer.…”
Section: Resultsmentioning
confidence: 94%
“…In another study on PLA and TiO 2 , Buzarovska and Grozdanov 14 found that adding TiO 2 to PLA had no significant influence on the characteristic temperatures such as T g , T c , and T m ; however, it increased the crystallinity of the composites. In another study, Alberton et al 15 found an increase in the mechanical properties of the PLA composites in the presence of the TiO 2 . In blends of PHB and CNFs, the obtained results showed that the addition of CNFs generally increased the mechanical properties of the PHB composites as compared with neat PHB; in addition, El-Hadi 12 found that adding CNFs improved the thermal properties of neat PHB.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Several research groups have reported an enhancement in mechanical performance of PLA with the incorporation of TiO 2 nanoparticles. Mechanical properties namely tensile strength (TS), Young’s modulus (YM), and elongation at break (EB) of PLA/TiO 2 composites fabricated via melt mixing technique were examined by Alberton et al [23]. While the values of TS and YM of the PLA were increased from ~53.66 MPa and ~3048 MPa into 58.28 MPa and 3237 MPa, respectively upon the incorporation of 1 wt.% TiO 2 owing to the reinforcing effect of TiO 2 nanoparticles, the EB value of PLA was found to be reduced from 3.56% to 3.00% with inclusion of 1 wt.% TiO 2 .…”
Section: Mechanical Propertiesmentioning
confidence: 99%